Extending the range of dual-zone permanent magnet synchronous motor control - Davydov A. E.; Bochenkov B. M.; Pankrats Yu. V. (Vestnik MGTU)
Achieving a twofold increase in the rotation speed of a permanent magnet synchronous motor while maintaining its power characteristics at the original level permits to increase the productivity and quality of material processing on metal-cutting machines. The theoretical study has been conducted using the mathematical model of a permanent magnet synchronous motor. The new control algorithm provides for two working zones: a nominal speed zone where the required power parameters are maintained (the first zone), and a high speed zone with a twofold increase in the rotation speed relative to the nominal (the second zone). To assess the efficiency of the developed algorithm, numerical modeling and comparative analysis with traditional control methods for a permanent magnet synchronous motor have been performed. The obtained results have demonstrated the advantages of the proposed approach permitting a twofold increase in the speed of the main drive of a metal-cutting machine without deteriorating its energy characteristics. The data of the theoretical study have been confirmed by simulation modeling of a closed system in the SimInTech software package. The developed control algorithm can be used to optimize the operation of main drives based on a permanent magnet synchronous motor as part of metalworking equipment.